2020
DOI: 10.3390/ma13030778
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Fracture and Fragmentation Characteristics of Metal Cylinder and Rings Subjected to Internal Explosive Loading

Abstract: Dynamic fracture and fragmentation characteristics of explosively driven rings and cylinders are important issues in the field of weapon effectiveness and protection. However, the comparison of fracture characteristics between metal cylinder and rings, and the fracture characteristics of the metal shells at different axial positions, are rarely touched. In the present work, a recovery tank was used to collect fragments, and witness plates were used to investigate the fragment spatial distributions. Before the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The experimental witness plates show a “random” group of fragment impacts. Figure 17 shows witness plates of fragment impacts from Arnold and Rottenkolber, 21 An et al, 24 and Swiderski et al 22 Although these witness plates indicate “random” fragment hits, the inserted lines, which “connect” three or more impacts, show that fragments hitting a target may be linked.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental witness plates show a “random” group of fragment impacts. Figure 17 shows witness plates of fragment impacts from Arnold and Rottenkolber, 21 An et al, 24 and Swiderski et al 22 Although these witness plates indicate “random” fragment hits, the inserted lines, which “connect” three or more impacts, show that fragments hitting a target may be linked.…”
Section: Resultsmentioning
confidence: 99%
“…The simulation is also compared with experimental witness plates created by Arnold and Rottenkolber, 21 An et al, 24 and Swiderski et al 22 The witness plates are similar and there is an indication that fragment hits and the same angle of projection form a straight line. Delivering fragment impacts as craters rather than points and including small yaw angle rotations would enable the simulation to be more accurate.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Table 5 shows the maximum principal tensile strain parameters of the three shell materials, where the failure strain values of 40CrMnSiB steel were measured by mechanical tests, and the maximum tensile failure strain values of 2024AL and OFHC copper were obtained from the literature [21] and [26] respectively, showing that there are significant differences in the ductility of the three materials. Studies of the fracture process of metal cylindrical shells under implosion loading have shown that the crack shape nucleation locations in the cylindrical shell space exhibit certain characteristics of random distribution [27,28], which is related to the inherent microdefects of the material itself. To describe the initial imperfection distribution of the shell material during the numerical simulation, the Mott random failure probability model [1] associated with shell fragmentation is introduced to define the variance of the unit failure strain such that each unit has a different failure strain.…”
Section: Failure Criteria and Initial Imperfectionmentioning
confidence: 99%